Refrigerator ownership and the nutrition-health trade-off: evidence from Chinese households - Zheng, Manli; Cai, Rong; Zhang, Li; Xu, Ke (Frontiers in Nutrition, 2025)
ObjectiveThis study investigates the dynamic effects of household refrigerator ownership on dietary patterns and the risk of overweight and obesity. The objective is to offer policy guidance for developing countries that are facing health challenges during their nutritional transition.MethodsThis study utilizes six waves of tracking data from the China Health and Nutrition Survey (CHNS, 1997–2011, n = 16,665). To address the estimation bias caused by endogeneity, the Control Function approach is employed. Furthermore, to elucidate the pathways through which refrigerator ownership influences overweight and obesity, a three-stage mediation model is used to assess the mediating effects of food purchases and processed food consumption on these outcomes.ResultsRefrigerator ownership significantly increases daily calorie intake by 39.1%. The ratios of energy derives from fat and protein rose by 0.104 and 0.018 percentage points, respectively, while the carbohydrate energy ratio decreases by 0.12 percentage points, indicating a shift towards a higher energy-dense diet. The mediating mechanism tests identify two pathways: an increased intake of high-fat and high-protein foods due to larger purchases and a rise in the consumption of processed foods. Health effects exhibit considerable heterogeneity; the risk of overweight increases with income, and the impact on older individuals is significantly greater than that on younger groups. Additionally, males face more than double the risk of obesity compared to females.ConclusionRefrigerator ownership significantly alters the dietary energy structure and raises the risk of overweight and obesity. These insights hold substantial theoretical and practical value in balancing technological advancements with public health objectives.